2021
DOI: 10.1029/2021ja029686
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Waves in the Distant Martian Environment: Implications for Mars' Sphere of Influence

Abstract: Mars has no global intrinsic magnetic field, but has localized crustal magnetic fields (Acuña et al., 1998). The interaction between the solar wind and plasma environment around Mars produces an induced mag-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Figures 5a and 5b show that the amplitudes of most left-hand and right-hand polarized waves are smaller than 0.2 nT, and the valid sample numbers peaking at 0.04-0.05 nT. Esman et al (2021) found that the semi-amplitudes of the whistler mode waves ranged from 0.01 to 1.34 nT based on MAVEN observations. In addition, the peak frequencies of left-hand and right-hand polarized waves are generally lower than 10 Hz, with their sample numbers peaking at around 4 Hz (Figures 5e and 5f).…”
Section: Statistical Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Figures 5a and 5b show that the amplitudes of most left-hand and right-hand polarized waves are smaller than 0.2 nT, and the valid sample numbers peaking at 0.04-0.05 nT. Esman et al (2021) found that the semi-amplitudes of the whistler mode waves ranged from 0.01 to 1.34 nT based on MAVEN observations. In addition, the peak frequencies of left-hand and right-hand polarized waves are generally lower than 10 Hz, with their sample numbers peaking at around 4 Hz (Figures 5e and 5f).…”
Section: Statistical Resultsmentioning
confidence: 88%
“…Esman et al. (2021) found that the semi‐amplitudes of the whistler mode waves ranged from 0.01 to 1.34 nT based on MAVEN observations. In addition, the peak frequencies of left‐hand and right‐hand polarized waves are generally lower than 10 Hz, with their sample numbers peaking at around 4 Hz (Figures 5e and 5f).…”
Section: Statistical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-step process to identify periods of possible wave signals in MAVEN MAG data was developed. The method is similarly described in Esman et al (2021), Esman et al (2022), andEsman (2022).…”
Section: A Semi-automated Methods For Wave Searchesmentioning
confidence: 99%
“…The result was a time series of magnetic fluctuation power for the entire data set, which indicated periods of possible wave activity with enhanced relative spectral power when compared to the overall average spectral power. We note that this method was similarly used and described by Esman et al (2021).…”
Section: Event Identification and Initial Analysismentioning
confidence: 99%